SenSALDO - Språkbanken Text (University of Gothenburg, 2024)
SenSALDO
A Swedish sentiment lexicon based on SALDO
Jacobo Rouces, Lars Borin, Nina Tahmasebi, Stian Rødven Eide
SenSALDO is a sentiment lexicon for Swedish based on the full-scale
Swedish semantic lexicon for language technology applications,
SALDO.
SenSALDO has been developed in the research
program Towards a knowledge-based culturomics, and with support
by the Swe-Clarin research
infrastructure, both funded by the Swedish Research Council.
SenSALDO v. 0.2 contains 12,287 word senses from SALDO labeled for
sentiment (prior lexical polarity) with one of the sentiment labels
"-1" (negative), "0" (neutral), or "1" (positive). The sentiment
labels have been assigned in a partly automatic, partly manual
process described in the publications listed below. The final set of
word senses has been manually curated.
In addition to the list of sentiment-labeled word senses, the
downloadable dataset contains a list of sentiment labeled text words
with their parts of speech (almost 85,000 words).
The word senses in SenSALDOS can have only one sentiment label
each, but a text word may appear with more than one label, in the
cases where a text word corresponds to more than one word sense, with
different sentiment labels. See the information in the file header.
If you use SenSALDO in research resulting in a publication, please
cite one or more of the publications listed below among your
references.

Publikationer • Publications

{publication 264720}
{publication 264719}
{publication 264721}

SenSALDO
Ett svenskt attitydlexikon baserat på SALDO
Jacobo Rouces, Lars Borin, Nina Tahmasebi, Stian Rødven Eide
SenSALDO är ett attitydlexikon för svenska som bygger på det
stora svenska semantiska språkteknologiska lexikonet
SALDO. SenSALDO har utvecklats inom det
VR-finansierade forskningsprogrammet Mot kunskapsbaserad storskalig
kunskapsutvinning ur svensk text, med stöd från
forskningsinfrastrukturen Swe-Clarin.
SenSALDO v. 0.2 innehåller 12.287 ordbetydelser ur SALDO 2.3 försedda
med någon av attitydetiketterna "-1" (negativ), "0" (neutral) eller
"1" (positiv). Etiketterna har tilldelats genom en process med
automatiska och manuella inslag, som beskrivs i de publikationer som
räknas upp nedan. Som sista steg i processen har alla de 12.287
ordbetydelserna korrigerats manuellt.
Förutom listan med attityduppmärkta ordbetydelser innehåller den
nedladdningsbara datamängden även en lista med attityduppmärkta
ordklassförsedda textord (nästan 85.000 ord).
SenSALDOS ordbetydelser har alltid bara en attitydetikett, men ett
textord kan ha fler än en i fall då det motsvarar mer än en
ordbetydelse med olika attitydvärden. Se informationen i filernas början.
Om du använder SenSALDO i forskning som resulterar i en
publikation, ber vi dig ange en eller flera av nedanstående
publikationer som referens.

Publikationer • Publications

{publication 264720}
{publication 264719}
{publication 264721}
SenSALDO
Keywords: Language Technology (Computational Linguistics); lexicon; Natural Language Processing; Språkbehandling och datorlingvistik